2018
DOI: 10.1186/s12881-018-0680-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetically determined high activities of the TNF-alpha, IL23/IL17, and NFkB pathways were associated with increased risk of ankylosing spondylitis

Abstract: BackgroundAnkylosing spondylitis (AS) results from the combined effects of susceptibility genes and environmental factors. Polymorphisms in genes regulating inflammation may explain part of the heritability of AS.MethodsUsing a candidate gene approach in this case-control study, 51 mainly functional single nucleotide polymorphisms (SNPs) in genes regulating inflammation were assessed in 709 patients with AS and 795 controls. Data on the patients with AS were obtained from the DANBIO registry where patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 68 publications
1
45
1
1
Order By: Relevance
“…There is a study which suggested that the rs2275913 of the IL17/IL23R pathway is associated with rheumatic heart disease (RHD) in South Indian populations (44). The associations found in the rs11209026 of IL23R and the rs187238 of IL18 genes suggest that a genetically determined high activity of the IL23/IL17 pathway was associated with increased risk of ankylosing spondylitis (45). Yu et al confirmed the association of SNPs of IL23R and IL17A with UC risk in Chinese Han population (46).…”
Section: Discussionmentioning
confidence: 99%
“…There is a study which suggested that the rs2275913 of the IL17/IL23R pathway is associated with rheumatic heart disease (RHD) in South Indian populations (44). The associations found in the rs11209026 of IL23R and the rs187238 of IL18 genes suggest that a genetically determined high activity of the IL23/IL17 pathway was associated with increased risk of ankylosing spondylitis (45). Yu et al confirmed the association of SNPs of IL23R and IL17A with UC risk in Chinese Han population (46).…”
Section: Discussionmentioning
confidence: 99%
“…Of all the interleukins secreted by Th17 cells, IL-1 β , IL-17, and IL-26 are most specific to Th17 cell response [ 2 , 8 11 ]. NF- κ B signaling, one of the significant pathways of the inflammatory process, is found to be involved in the etiology of AS [ 12 ]. NF- κ B induces the expression of TNF- α , IL-1 β , and other proinflammatory cytokines [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylated STAT dimers enter the nucleus and act on downstream target genes. IL-23R has been identified to associate with multiple diseases, including alopecia areata (rs10889677) and nephropathy (rs10805303) (Figure 3) (Safrany et al, 2011;Yu et al, 2012;Huang et al, 2016;Qin et al, 2016;Poomarimuthu et al, 2018;Sode et al, 2018;Zhong et al, 2018;Kramer et al, 2019;Loures et al, 2019;Ruyssen-Witrand et al, 2019;Tabatabaei-Panah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%